Oncostatin-M Does Not Predict Treatment Response in Inflammatory Bowel Disease in a Pediatric Cohort. Issue 3 (September 2021) - Ezirike Ladipo, Jennifer; He, Zhaoping; Chikwava, Kudakwashe; Robbins, Katherine; Beri, Jonathan; Molle-Rios, Zarela
ABSTRACT: Objectives: This study aimed to determine whether mRNA expression of oncostatin-M (OSM) and its receptor (OSMR) in initial, pre-treatment intestinal biopsies is predictive of response to tumor necrosis factor antagonists (anti-TNF) in a pediatric inflammatory bowel disease (IBD) cohort. Secondary outcomes correlated OSM and OSMR expression with demographic variables; IBD type, extent, phenotype, and severity; laboratory values; and endoscopic findings. Methods: A retrospective chart review was conducted on 98 pediatric patients. Patients' clinical courses were stratified as follows: failed anti-TNF (n = 14), quiescent on anti-TNF (n = 36), anti-TNF naïve (n = 19), and age-matched non-IBD controls (n = 29). The mRNA from each patient's pre-treatment ileal or colonic biopsy was isolated, and expression of OSM and OSMR was analyzed. Results: There was no difference in OSM or OSMR expression among the three IBD groups; however, expression was significantly higher in patients with IBD than non-IBD controls ( P < 0.001). OSM and OSMR were more highly expressed in patients with ulcerative colitis (UC) with a Mayo score of 3 ( P = 0.0092 and P = 0.0313, respectively). High OSM expression correlated with severe disease activity indices at diagnosis ( P = 0.002), anemia at diagnosis ( P = 0.0236), and need for immunomodulators ( P = 0.0193) and steroids ( P = 0.0273) during patients' clinical courses. Conclusions: OSM and OSMR expression were not predictive of response to anti-TNF in our pediatric cohort. OSM expression did correlate with IBD compared with healthy controls as well as with several clinical indicators of severe IBD. Abstract : Supplemental Digital Content is available in the text